Penguatan Pengelolaan Keuangan BUMDes Sebagai Upaya Menuju Desa Mandiri di Desa Kebontunggul Mojokerto - Aristha Purwanthari Sawitri; Taudlikhul Afkar; Martha Suhardiyah; Suharyanto (Jurnal Pemberdayaan Masyarakat, 2020)
The purpose of the implementation of this community service activity is to provide an understanding of the financial management of BUMDes. The problem faced by partners is that bumdes financial management has not been properly managed, resulting in the optimal governance of BUMDes in the partner village. The un availability of accommodated resources in the village is one of the causes of the unsanying of local potential in partner villages and their surroundings. This method of community service implementation is carried out by providing training on the importance of accounting management as a form of business management accountability and providing assistance to partners in compiling financial statements in accordance with financial accounting standards (SAK). The result of this community service activity is that BUMDes managers are able to compile BUMDes financial statements in a simple way including cash statements, income statements, capital change reports and financial position statements. Although the results of financial reporting compiled by partners are still very simple, this reporting has been done with SAK and it is expected that in the future the management of the partner's financial system is well organized.